A new species of Hammerschmidtiella Chitwood, 1932 (Nematoda, Thelastomatidae) parasite of the brown cockroach Periplaneta brunnea Burmeister, 1838 (Blattodea, Blattidae) from Argentina - Camino, Nora Beatriz (2012)
A new species of the genus Hammerschmidtiella, H. eltalaensis sp. nov. parasitizing a brown cockroach Periplaneta brunnea Burmeister from El Tala river, Catamarca, Argentina, is described and illustrated. It is characterized by having the cuticle striated, without lateral alae, mouth with three toothed lips and eight labial papillae, amphids small and pore shaped, buccal capsule short, wide, with four mobile teeth, oesophagus with metacorpus valvate, isthmus cylindrical and thin surrounded by nerve ring, and a rounded basal bulb heavily muscled and valvate, the vulva is slightly protruding and lies in the anterior third of the body, didelphic, prodelphic, eggs small and elongate, the male with one spicule, without gubernaculum, the genital papillae arranged in one pair of small preanal papillae, and two postanal papillae, one pair is the base of the tail appendage. Tail appendage very long, thin, and reaching almost one third of the length of the body in the female. In the male the posterior end of the body abruptly truncated posterior to anus with spine-like long tail appendage.